Exacerbation of Viral and Autoimmune Animal Models for Multiple Sclerosis by Bacterial DNA - Tsunoda, Ikuo (Brain Pathol, 2006)
Theiler's murine encephalomyelitis virus (TMEV) infection and relapsing‐remitting experimental allergic encephalomyelitis (R‐EAE) have been used to investigate the viral and autoimmune etiology of multiple sclerosis (MS), a possibleTh1‐type mediated disease. DNA immunization is a novel vaccination strategy in which few harmful effects have been reported. Bacterial DNA and oligodeoxynucleotides, which contain CpG motifs, have been reported to enhance immunostimulation. Our objectives were two‐fold: first, to ascertain whether plasmid DNA, pCMV, which is widely used as a vector in DNA immunization studies, could exert immunostimulation in vitro; and second, to test if pCMV injection could modulate animal models for MS in vitro. We demonstrated that this bacterially derived DNA could induce interleukin (IL)‐12, interferon (IFN)γ (Th1‐promoting cytokines), and IL‐6 production as well as activate NK cells. Following pCMV injections, SJL/J mice were infected with TMEV or challenged with encephalitogenic myelin proteolipid protein (PLP) peptides. pCMV injection exacerbated TMEV‐induced demyelinating disease in a dose‐dependent manner. Exacerbation of the disease did not correlate with the number of TMEV‐antigen positive cells but did with an increase in anti‐TMEV antibody. pCMV injection also enhanced R‐EAE with increased IFNγ and IL‐6 responses. These results caution the use of DNA vaccination in MS patients and other possible Th1‐mediated diseases.